Brunei : history, Islam, society and contemporary issues - Ooi, Keat Gin, 1959- (Abingdon, Oxon : Routledge, 2016)
'Brunei, although a relatively small state, is disproportionately important on account of its rich resource base. In addition, in recent years the country has endeavoured to play a greater role in regional affairs, especially through ASEAN, holding the chair of the organisation in 2013, and also beyond the region, fostering diplomatic, political, economic and educational ties with many nations. This book presents much new research and new thinking on a wide range of issues concerning Brunei largely drawn from Bruneian academics. Subjects covered include Brunei's rich history - the sultanate formerly had much more extensive territories and was a key player in regional affairs; the country's economy, politics, society and ethnicities; and resource issues and international relations'--
Includes bibliographical references and index.
Keywords: Brunei -- Social conditions; Brunei -- Foreign relations; Brunei -- History